2022
DOI: 10.3389/fpls.2022.976901
|View full text |Cite
|
Sign up to set email alerts
|

RNAseq, transcriptome analysis and identification of DEGs involved in development and ripening of Fragaria chiloensis fruit

Abstract: Fragaria chiloensis (Chilean strawberry) is a native species that produces fruit with an exotic pinkish color and a fruity aroma. It has a non-climacteric pattern of fruit ripening, and it is the mother of the commercial Fragaria x ananassa. The ripening of F. chiloensis fruit seems stimulated by ABA, and a complete set of genes participate in its softening, color, and aroma development. In addition, a set of transcription factors regulate the entire process, but few of them have been described. Over the last … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
5
0
1
Order By: Relevance
“…In Fragaria chiloensis, two NCEDs and two CCDs were identified within the transcriptome prepared from fruit samples [37]. In general, the number of CCD genes identified in the genome of different fruit species is reduced compared to the number described in non-fruit species (30 in oilseed rape; 19 in tobacco) [35].…”
Section: Discussionmentioning
confidence: 99%
“…In Fragaria chiloensis, two NCEDs and two CCDs were identified within the transcriptome prepared from fruit samples [37]. In general, the number of CCD genes identified in the genome of different fruit species is reduced compared to the number described in non-fruit species (30 in oilseed rape; 19 in tobacco) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional analysis allows us to explore the molecular mechanism of the cells to Cd stress. The possible function of DEGs can be deduced because the genes within the same pathway usually cooperate with each other to run their biological function [39]. Although many studies have demonstrated that Cd exposure has toxic impact on the reproductive system, leading to a decreased fertility [11], the underlying mechanism is still unclear.…”
Section: Transcriptional Response Of Gc-1 Spg Cells To CD Exposurementioning
confidence: 99%
“…Genes annotated as NCED/CCD and PYR/PYL were selected from the Genome Database of Rosaceae [66] using Malus domestica, Prunus persica, Rosa chinensis and F. x ananassa as reference species. Then, a comparative mapping of selected sequences and a F. chiloensis transcriptome was carried out as a way to identify their orthologs [37]. Sequences were aligned using MAFFT version 7…”
Section: F Chiloensis Gene Sequencesmentioning
confidence: 99%